Junk Food Advertisements with Free Offer: Their Repercussions in the Minds of Children in the Age Group of 3-10 Years - Ramesh Kumar, S. (Indian Journal of Marketing, 2011)
Television (TV) food advertising has attracted attention for its potential role in promoting unhealthy eating among children. Children aged 2 to 11 years spend on an average, three hours a day watching television, which is more than with any other medium, and children see about 5,500 food advertisements per annum (Gantz W et al.,). Average children view over 40,000 commercials a year. Most of them are for candies, cereals, toys, and fast food restaurants. According to UK Children’s Secretary Ed Balls, the average child in the United Kingdom watches approximately 10,000 television ads per annum, and can recognize 400 brands by age 10. Social cognitive theory (Bandura, 1994) predicts that children learn from behaviour symbolically modelled en masse media, as well as from role models in their immediate social environment. Arnas (2006) reported that TV advertisements affected young children’s unhealthy food consumption. In general, there is good research evidence that advertising impacts on children’s food preferences and consumption (Hastings et al., 2003). Research into the effects of food advertising on children is increasing. One of the reasons why TV has such an effect is because food is the most frequently advertised product category on children’s TV programming, and it has been established that exposure to food advertisements effectively promotes consumption of the advertised products (Halford 2004). Previous studies conducted in developed countries have shown that the vast majority of food advertising targeted at children is for food of poor nutritional value, whereas, such foods as fruit, vegetables, and whole grains are seldom advertised. A number of surveys have found greater TV viewing is associated with consumption of energy dense foods and drinks (Campbell 2006).